Pregnancy and chronic nephropaties: maternal renal risk: Implications for so-called "therapeutic abortion " - Stirati, G.; Pierucci, A.; Boccia, E.; Mazzoni, C.; Colonnelli, R.; Rocca, A. R.; Pachì, A.; Spagnolo, A. G. (Medicina e Morale, 1995)
In this study, based on a case of pregnancy in a patient suffering from IgA nephropaty (Berger's disease), two problems are discussed: risk for materna! renal function in chronic renal disease, and "indications" far so-called "therapeutic abortion". Physiological changes of renal function and blood arterial pressure in pregnancy whose knowledge is essential for a correct clinical evaluation of the individuai patient, are underlined. Personal experience and review of the recent literature about the effects of pregnancy on renal function in women affected by chronic renal disease are presented. The authors conclude that pregnancy does not per se exacerbate renal diseases, at least in patients whose renal function is nearly norma! at the beginning of pregnancy. Prognosis is worse in the presence of renal failure (serum creatinine > 1.4 mg/dl). Finally some ethical remarks on so-called "therapeutic abortion" are expressed, underlin ing that - because of current advances in obstetrics, nephrology and neonatology - abortion could be always avoidable. Moreover we draw the attention of physicians to the constant teaching of the Catholic Church confirming the value and inviolability of human life.